Induced sputum: a window to lung pathology. (22nd July 2009) - Nicholas, Ben; Djukanović, Ratko
Abstract : Sputum is recognized as a sampling method for the monitoring and assessment of chronic lung diseases such as asthma, COPD (chronic obstructive pulmonary disease) and cystic fibrosis. Sputum samples the central airways and its protein components (e.g. mucins and cytokines), cellular components (e.g. eosinophils and neutrophils) and microbiological components (e.g. viruses and bacteria) can be used as markers of disease severity, exacerbation, susceptibility or progression. This paper describes the basic constituents of induced sputum and how these influence the quantification and identification of novel biomarkers of chronic lung diseases using techniques such as proteomics.